2023
DOI: 10.3389/fphar.2023.1271613
|View full text |Cite
|
Sign up to set email alerts
|

Copper homeostasis and cuproptosis in tumor pathogenesis and therapeutic strategies

Chenbin Bian,
Zhuangzhuang Zheng,
Jing Su
et al.

Abstract: Copper is an indispensable micronutrient for the development and replication of all eukaryotes, and its redox properties are both harmful and beneficial to cells. An imbalance in copper homeostasis is thought to be involved in carcinogenesis. Importantly, cancer cell proliferation, angiogenesis, and metastasis cannot be separated from the effects of copper. Cuproposis is a copper-dependent form of cell death that differs from other existing modalities of regulatory cell death. The role of cuproptosis in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Usually, a sophisticated network involving the Snail repressor and the copper-dependent LOX-like proteins controls the transcription of E-cadherin. It has been observed that copper can influence the regulation of the epithelial-mesenchymal transition [40,49,50]. After discussing the crucial role of copper in cancer growth, it is important to emphasize that the elevated copper levels present in cancer can be specifically targeted to eliminate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, a sophisticated network involving the Snail repressor and the copper-dependent LOX-like proteins controls the transcription of E-cadherin. It has been observed that copper can influence the regulation of the epithelial-mesenchymal transition [40,49,50]. After discussing the crucial role of copper in cancer growth, it is important to emphasize that the elevated copper levels present in cancer can be specifically targeted to eliminate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring a balance of copper ions in biological systems is crucial to preventing atherosclerosis and cardiovascular diseases associated with it [29]. Disruption in the regulation of copper levels is also believed to play a role in the process of carcinogenesis [30]. The concentrations of copper ions can function as a vital indicator of cancer progression [27].…”
Section: Copper's Biological Rolementioning
confidence: 99%
“…Cuproptosis takes place when copper binds to lipoylated enzymes in the tricarboxylic acid (TCA) cycle, resulting in the aggregation of proteins, proteotoxic stress, and, ultimately, cancer cell death [42]. Nevertheless, the influence of cuproptosis on malignant tumours remains incompletely comprehended from a clinical standpoint [30]. In investigations concerning the anticancer efficacy of copper (II) complexes and other metallic coordination compounds on breast and lung cancer cells, the copper (II) complex displayed encouraging cytotoxic potency.…”
Section: Copper In Cancermentioning
confidence: 99%
“…On the one hand, Cu is an indispensable micronutrient for the development and homeostasis of all living organisms [1]. For example, it is an important cofactor of enzymes, including copper-zinc superoxide dismutase (SOD 1), cytochrome c oxidase (CCO), and lysyl oxidase (LOX) [2]. On the other hand, excessive Cu in the aquatic environment leads to the accumulation of reactive oxygen species (ROS) in aquatic organisms, leading to DNA damage, apoptosis, and tissue structure damage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%